Patterns and Trends of Development Communication Studies Conducted by Students of a State University in the Philippines - Madrid, Avril Adrianne DG; Cagasan, Editha G. (Annals of Tropical Research, 2016)
As part of their academic requirements, graduate and undergraduate development communication (DevCom) students of the Visayas State University (VSU) in the Philippines are required to write a thesis. This study aimed to identify patterns and trends in DevCom research by VSU students. It examined the development context, focus, theoretical bases, methods used and the major findings of their research. A total of 203 studies were content analyzed. Results showed that between 1979 to 1989, most of the students’ research were on agriculture, mass media and health. In the recent years, there has been an accommodation of other development issues including health, environment and information communication technology. Most of the studies, however, focused mainly on two areas of communication research – audience and effects. Although communication books list more than 200 communication theories, only 18 were used in the students’ research. Most of the studies used quantitative methods, but an increase in the number of qualitative studies or a combination of the two was noticed in recent years. A good number of the studies tested relationships among variables. The major findings of most of these studies were: (1) information exposure significantly influenced knowledge, attitude and practice; and (2) the socio-demographic variables that most often emerged to have significant relationship with knowledge, attitude and practice were age, sex, educational attainment and income.